Remarks With Prime Minister Anthony Albanese of Australia, Prime Minister Narendra Modi of India, and Prime Minister Fumio Kishida of Japan at the Quadrilateral Security Dialogue Leaders Summit in Hiroshima, Japan May 20, 2023 - Biden, Joseph R (Daily Compilation of Presidential Documents, 2023)
Climate action, disaster management, strategic technologies, reliable supply chains, health security, maritime security, counterterrorism are examples of areas in which our positive cooperation is increasing. Free and open international order based on the rule of law is under threat. Subjects: Association of Southeast Asian Nations (ASEAN); Australia, Prime Minister; Australia, relations with U.S.; India, Prime Minister; India, relations with U.S.; Indo-Pacific, economic and security cooperation; Japan, President Biden's visits; Japan, Prime Minister; Japan, relations with U.S.; Pacific Islands Forum; Quadrilateral Security Dialogue; Renewable energy sources and technologies.